Crystallisation in polymer nanocomposites - Jog, Jyoti Prakash (Materials Science and Technology, 2006)
Polymer nanocomposites are of interest as they exhibit extraordinary properties compared with the base polymer. The second phase dispersed in the polymer matrix can be carbon nanotubes, semi-conducting inorganic nanoparticles or layer silicates such as clay. Crystallisation in these materials is also of great interest. Polymers exhibit structures at various scales (e.g. lamella, unit cell and spherulites) and the presence of a second phase has a profound effect on crystallisation. General trends observed include acceleration/retardation of crystallisation, changes in spherulite morphology and, in a few cases, changes in the crystal structure. All these observations relate to the presence of a micrometre scale second phase. However, when the dimensions of the second phase are close to the chain dimensions, the effects on crystallisation become particularly interesting. An attempt is made in the present review to address the effect of a nanoscale second phase on aspects such as isothermal and non-isothermal crystallisation, spherulite growth, phase transformation and polymorphism.
Keywords: clay; crystallisation; Nanocomposites; polymer matrix composites

Crystallization and phase transformation kinetics of poly(1-butene)/MWCNT nanocomposites - Wanjale, Santosh D.; Jog, Jyoti Prakash (Polymer, 2006)
Poly(1-butene)/MWCNT nanocomposites were prepared by simple melt processing technique. Crystallization, crystal-to-crystal phase transformation and spherulitic morphology were studied using differential scanning calorimetry (DSC), wide angle X-ray diffraction (WAXD) and optical microscopy (OM). The non-isothermal crystallization exhibited higher values of Z, derived from Avrami theory and lower values of F(T) obtained from Avrami-Ozawa analysis, while the isothermal crystallization revealed a significant increase in crystallization temperatures and lower crystallization half times compared to pristine PB. The observed changes in the crystallization kinetics were ascribed to the enhanced nucleation of PB in the presence of MWCNT. The nucleating activity calculated from the non-isothermal crystallization data revealed that the MWCNTs provide an active surface for the nucleation of PB. The optical micrographs exhibited significantly smaller crystallites with disordered morphology for the nanocomposites compared to the well defined spherulitic morphology for pristine PB. The rate of phase transformation from kinetically favored tetragonal to thermodynamically stable hexagonal form was noticeably enhanced as evidenced by the reduction in the half time for phase transformation from 58 h to 25 h for PB reinforced with 7% MWCNT. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: MWCNT; Phase transformation; poly(1-butene)

Copolyester nanocomposites based on carbon nanotubes: reinforcement effect of carbon nanotubes on viscoelastic and dielectric properties of nanocomposites - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Polymer International, 2008)
Nanocomposites based on an amorphous copolyester, poly(ethylene glycol-co-cyclohexane-1,4-dimethanol terephthalate) and carbon nanotubes were fabricated using a simple melt processing technique. The reinforcement effect of carbon nanotubes in the copolyester was investigated experimentally using different approaches based on dynamic mechanical analysis, theology and dielectric analysis. The nanocomposites show a mechanical reinforcement effect with significant increase in the stiffness especially in the rubbery regime with increasing nanotube content. An increase in T-g and a decrease in damping are seen, which are derived from the presence of a percolating superstructure of the filler. Rheological experiments show an increase in storage modulus up to four orders of magnitude. Viscolelastic characterization shows that the percolation threshold is at 3 wt% of nanotubes. Dielectric relaxation spectroscopy confirms the presence of this percolating structure. We conclude that the responses of both rheological and electrical properties are different, although both are related to the formation of a percolating network superstructure of the filler. (c) 2007 Society of Chemical Industry.
Keywords: Carbon nanotubes; dielectric analysis; nanocomposites.; reinforcement; viscoelastic properties

Characterisation of copolymer, poly (hydroxybutyrate-co-hydroxyvalerate) (PHB-co-PHV) produced by halomonas campisalis (MCM B-1027), its biodegradability and potential application - Kulkarni, Snehal O.; Kanekar, Pradnya P.; Jog, Jyoti Prakash; Patil, Prashant A.; Nilegaonkar, Smita S.; Sarnaik, Seema S.; Kshirsagar, Pranav R. (Bioresource Technology, 2011)
Characterisation of polyhydroxyalkanoate (PHA) film produced by haloalkalitolerant Halomonas campisalis (MCM B-1027) in 14 L SS fermenter revealed it to have composition of monomer units, HB:HV as 96:4 as analysed by (1)H NMR indicating the PHA as a co-polymer of PHB-co-PHV, molecular weight by gel permeation chromatography as 2.08 x 10(6), melting temperature 166.51 degrees C, tensile strength 18.8 MPa; two relaxations namely beta transition corresponding to the glass rubber transition and alpha transition corresponding to crystalline relaxation by Dynamic Mechanical Thermal analysis and only one relaxation corresponding to MWS interfacial polarisation with activation energy of 129 kJ/mol by broadband dielectric spectroscopy. Optical microscopic studies showed typical Maltese-cross pattern of spherulites. The PHA film was found to be biodegradable by standard ASTM method as well as by soil burial method. The leak proof polymer bags prepared from the film could be used as a packaging material. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable polymer; Copolymer PHB-co-PHV; Dielectric relaxation spectroscopy; Dynamic mechanical analysis; Halomonas

Controlling stoichiometry in low temperature synthesis of La0.7Sr0.3MnO3 nanoparticles - Azarifar, Ali; Yadav, P. A.; Chawla, A. K.; Jog, Jyoti Prakash; Patil, S. I.; Chandra, Ramesh; Ogale, S. B. (Advanced Science Letters, 2011)
Nanoparticles of complex oxides (<20 nm) are desirable for several applications in view of the diverse range of physical properties of such oxides. However the simultaneous presence of multiple cation precursors makes the corresponding chemical synthesis non-trivial with possible intermediate evolution of secondary phases. Such phases could react at high temperatures to form the desired stoichiometry, but this process is diffusion limited and can lead to larger particles. In this work we examine the role of three different reaction and growth controlling additives, namely dextran, citric acid and hexamine, on the synthesis of the well known colossal magneto-resistive (CMR) manganite La0.7Sr0.3MnO3. We demonstrate that phase evolutions differ significantly in the three cases, and the physical properties of the products also differ dramatically. Only dextran is shown to yield the desired phase with faceted nanoparticles at as low a temperature as 600 degrees C. A high saturation moment of similar to 47 emu/gm is realized at 10 K with a good square hysteresis loop. In 650 degrees C annealed sample, room temperature magnetization of similar to 15 emu/gm was obtained, which brings the nanoparticles in the applicability domain.
Keywords: Citric acid; Complex Oxide; Dextran; Hexamine; hydrothermal

Carbon nanoscrolls by pyrolysis of a polymer - Yadav, Prasad; Warule, Sambhaji; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2012)
3D network of carbon nanoscrolls was synthesized starting from pyrolysis of poly(acrylic acid-co-maleic acid) sodium salt. It is a catalyst-free process where pyrolysis of polymer leads to formation of carbon form and sodium carbonate. Upon water soaking of pyrolysis product, the carbon form undergoes self-assembly to form carbon nanoscrolls. The interlayer distance between the walls of carbon nanoscroll was found to be 0.34 nm and the carbon nanoscrolls exhibited a surface area of 188 m(2)/g as measured by the BET method. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanoscrolls; Polymer; Pyrolysis; supercapacitor